Factors influencing Covid-19 vaccine acceptance across subgroups in the United States: Evidence from a conjoint experiment - Kreps, S.E.; Kriner, D.L. (Vaccine, 2021)
•Effects of vaccine attributes on willingness to vaccinate vary across subgroups.•These heterogeneous effects can inform targeted outreach.•Flu vaccination, safety beliefs and contact with covid-19 partially explain variation.•Concerns about fertility unlikely to explain gender gap in vaccine acceptance. Public health officials warn that the greatest barrier to widespread vaccination against Covid-19 will not be scientific or technical, but the considerable public hesitancy to take a novel vaccine. Understanding the factors that influence vaccine acceptance is critical to informing public health campaigns aiming to combat public fears and ensure broad uptake. Employing a conjoint experiment embedded on an online survey of almost 2,000 adult Americans, we show that the effects of seven vaccine attributes on subjects’ willingness to vaccinate vary significantly across subgroups. Vaccine efficacy was significantly more influential on vaccine acceptance among whites than among Blacks, while bringing a vaccine to market under a Food and Drug Administration Emergency Use Authorization had a stronger adverse effect on willingness to vaccinate among older Americans and women. Democrats were more sensitive to vaccine efficacy than Republicans, and both groups responded differently to various endorsements of the vaccine. We also explored whether past flu vaccination history, attitudes toward general vaccine safety, and personal contact with severe cases of Covid-19 can explain variation in group vaccination hesitancy. Many subgroups that exhibit the greatest Covid-19 vaccine hesitancy did not report significantly lower frequencies of flu vaccination. Several groups that exhibited greater Covid-19 vaccine hesitancy also reported greater concerns about vaccine safety generally, but others did not. Finally, subgroup variation in reported personal contact with severe cases of Covid-19 did not strongly match subgroup variation in vaccine acceptance.